Renewable Energy Consumption and Economic Growth in Argentina: A Multivariate Co-integration Analysis - Khobai, Hlalefang (International Journal of Energy Economics and Policy, 2021)
This paper applied the ARDL bounds test approach and the VECM test technique to examine the long run relationship and direction of causality between renewable energy consumption and economic growth in Argentina. Quarterly time series data was employed in this study covering a period between 1990 and 2018. Trade openness, capital and employment were included in the study to form a multivariate framework. The results established that there is a long run relationship between the variables. The VECM test technique confirmed a unidirectional causality flowing from economic growth to renewable energy consumption. This implies that energy conservation policies may not harm the economic growth. The study, therefore, suggest that an appropriate and effective energy policy should be implemented in the long run. Keywords: Renewable energy consumption, Economic growth, Causality, Argentina JEL Classifications: D04, C32, Q47, Q42, Q01 DOI: https://doi.org/10.32479/ijeep.6375